Pesticide Residues in Fresh Fruit and Vegetables from Farm to Fork in the Kampala Metropolitan Area, Uganda - Charles Ssemugabo; Asa Bradman; John C. Ssempebwa; Fenna Sillé; David Guwatudde (SAGE Publishing, 2022)
This study assessed concentrations of pesticide residues in fruits and vegetables from farm-to-fork in Kampala Metropolitan Area, Uganda. A total of 160 samples of fruit and vegetables collected from farms, markets, streets, restaurants and homes were analysed using liquid chromatography-tandem mass spectrometry; and Gas Chromatograph-Mass Spectrometer for dithiocarbamates. Multiple pesticide residues were detected in majority of the samples (95.6%). The proportions of the most frequently detected pesticides residue classes were organophosphates (91.3%), carbamates (67.5%), pyrethroids (60.0%) dithiocarbamates (48.1%) and neonicotinoids (42.5%). Among organophosphates, propotamophos, acephate, fonofos, monocrotophos and dichlorvos were the most detected active ingredients; aminocarb, methomyl and pirimicarb were the commonly detected carbamates; while imidacloprid, a neonicotinoid and lambda-cyhalothrin, pyrethroid were also highly detected. Twenty-seven pesticide were tested at all stages, of which the concentrations either decreased or increased along the chain. Multiple pesticide residues occurred in commonly consumed fruit and vegetables with decreasing or increasing concentrations from farm-to-fork.